Post Traumatic Stress Disorder (PTSD) Guidance After Earthquake in SMP N 1 Sembalun East Lombok - FitriAulia; Marfuatun; Nurul Anwar (Simposium Antar Bangsa Seminar dan Workshop)
This study aims to see how much psychological treatment of earthquake victims in Lombok that occurred in mid-2018. The targets were chosen based on the location of the earthquake affected in severe conditions namely in Sembalun 1 Public Middle School. PTSD is a service after the trauma of earthquake victims. PTSD can be done after an earthquake occurs within a certain time to ensure the victim's condition, whether he is still traumatized or has fully recovered. The method used is Kurt Lewin's Action Research model, namely doing treatment in this cycle consists of four steps, namely: (1) planning, (2) action or action, (3) observation, (4) reflection. Based on the results of the implementation of the activities that have been carried out, it can be concluded into the following 4 things: first, based on the results of the PTSD diagnostic instrument students at SMPN 1 Sembalun are on the criteria of high trauma. Second, based on DCM results (List of Problem Checks) Students experience 5 aspects of symptoms of Traumatic Stress Disorder, namely physical, emotional, mental, behavioral and spiritual symptoms. Third, from the activities that have been carried out, students become more relaxed and have the enthusiasm to re-pursue their dreams. Fourth, students still need psychological trauma after trauma so that they can still develop optimally in various aspects of development.